فعالية استخدام بطاقة الصور في تعليم المفردات لتنمية مهارة الكلام لتلاميذ الصف الخامس بمدرسة مجاهدين الابتدائية سورابايا - Nur Wicaksono, Hanang; Hermawan, Hermawan; Nasaruddin, Nasaruddin (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
This study aims to determine the effectiveness of using Flashcards media in learning vocabulary to improve students' Arabic speaking skills of Mujahidin Elementary School students at class 5B in Surabaya, East Java, because their speaking skills are weak, so teachers need learning media that can make students more enthusiastic after that and easy to memorize vocabulary. This study is a research with experimental method in quantitative approach that aims to test a theory or hypothesis which was given two assessments before and after teaching the material with the media. The data collection methods used are observation, interview, test, and questionnaire. The data analysis technique used is paired sample T-test with null and alternative hypothesis (H0 and H1) from the results of pre-test and post-test. The results showed (1) The use of Flashcards media in learning Arabic vocabulary is effective to improve students' speaking skills; (2) Students' speaking ability can be measured from the results of pretest and posttest scores; (3) The results of data analysis showed the paired sample T-test that a value of “Tcount” is 8,74 more than “Ttable” is 2,09 at the 5% significance level and 2,87 at the 1% significance level. And then H0 is rejected and H1 is accepted, the meaning is the use of Flashcards in learning vocabulary is very influential and effective for improving Arabic speaking skills of students.